1587. Analysis of Breakthrough Blood Stream Infections in Left Ventricular Assist Device Recipients Managed With Chronic Antimicrobial Suppressive Therapy. (26th November 2018) - Jandhyala, Deeksha; O'horo, John C; Wright, Alan J; Walker, Randall C; Stulak, John; Bran, Andres; Baddour, Larry M; Farid, Saira; Sohail, M Rizwan
Abstract: Background: Left ventricular assist devices (LVAD)-associated infections are associated with fivefold higher 1-year mortality. Published literature is insufficient to inform clinicians regarding optimal management of bloodstream infection (BSI) in patients LVAD recipients. In particular, it is unclear which episodes of BSI may result in occult hematogenous seeding of the device surfaces, and therefore should be managed with chronic suppressive therapy (CAS). We aim to describe BSI, CAS, and breakthrough BSI in our LVAD population. Methods: We retrospectively reviewed 332 episodes of all LVAD infections at Mayo Clinic from 2007 to 2015. We categorized BSI as LVAD related/associated and LVAD nonrelated as defined by established criteria in the cardiac device literature. Our primary outcome was to describe breakthrough BSI in LVAD related and nonrelated infections in patients receiving CAS and those who were not. Results: We identified 68 episodes of bacteremia in our LVAD population. Of these, 55 were proven BSI (see Fig 1). In our study cohort, 45/55 (82%) were male and median patient age was 62 years. A majority of LVAD implants were destination therapy 34/55 (62%) and 35/55(64%) had a central line in place at the time of BSI. Twenty patients had non-VAD-related BSI and nine of these (9/20, 45%) patients were placed on CAS with two of these (2/9, 22%) had subsequent breakthrough BSI, whereas 11/20 (55%) were not placed on CAS with no breakthrough infections seen (Figure 1). Conclusion: Our preliminary data suggest that routine use of CAS for non-VAD-related BSI is not necessary as only a minority go on to have breakthrough BSI. Limiting unnecessary use of antibiotics will have significant implications for stewardship and preventing emergence of resistance. Disclosures: L. M. Baddour, UpToDate: Collaborator, Royalty payment. M. R. Sohail, TyRx Inc: Investigator, Research support; Medtronic Inc: Investigator, Research support; Medtronic Inc: Consultant, Speaker honorarium; Spectranetics: Consultant, Speaker honorarium; Boston Scientific Corp: Consultant, Speaker honorarium.